Analytical method applied for perfluororinated chemicals in water, sediment and fish by liquid chromatography with tandem mass spectrometry - Anh, Duong Hong; Ngoc, Nguyen Thuy; Quang, Dinh Phan; Tuyen, Le Huu; Kim, Truong Thi; Vi, Phung Thi; Viet, Pham Hung (VNU Journal of Science: Natural Sciences and Technology, 2017)
Abstract: 12 perfluororinated chemicals including perflourocarbocylic acids and perfluoroankyl sulfonates (containing C4 to C12)  in environmental media such as water, sediment and fish were deternined by liquid chromatography with tandem mass spectrometric detector (LC-MS/MS) using  weak anion exchange cartridge (WAX) in solid phase extraction for sample preparation.  The result of method validation showed that the recoveries of 12 PFCs for water and fish samples were in a range from 87 to 112% ( 4-17% CV)  and a range from  81 to125% (3-12% CV), respectively. The method was a reliable analysis for 10 PFCs compounds of sediment sample which recieved the recoveries in a range from 80 to121% (3-16% CV), except PFUdA and PFDoA. The detection limits of 12 PFCs were from 0.06 to 0.6 ng/L for water and from 0.01 to 0.06 ng/g for sediment and fish samples.